TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG VULVA HYGIENE SAAT MENSTRUASI DI SMA ADVENT TOMPASO - Angelica Stephani Meriam; Monalisa Sitompul (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
The cleanliness of the vulva is an important thing that deserves attention, especially when a person is menstruating. By maintaining the cleanliness of the vulva we can avoid and prevent the emergence of various health problems in the female reproductive organs. Vulva hygiene behavior is very important to apply when menstruating because when menstruating the vulva and other reproductive organs become more susceptible to infection. The purpose of this study was to find out the knowledge of young women about vulva hygiene during menstruation at Advent Tompaso High School. The research method used is quantitative with a preexpermental design one group pretest-posttest with research instruments in the form of multiple choice questions about the knowledge of vulva hygiene at the time of menstruation. The number of respondents in this study was 100 students in grades 1-3 of high school. It was found that the paired T-test value of 0,000 <0.05 significance which can be interpreted to mean that there was a significant increase in adolescent girls knowledge about vulva hygiene. Advice that can be given in the learning process in school in order to provide more information about the importance of maintaining vulva hygiene to improve the level of health in the reproductive organs.